The Relationship Of Attitude Of Pregnant Mothers With ANC (Antenatal Care) Compliance - Riza Febrianti (Institute of Computer Science (IOCS), 2022)
Antenatal care (ANC) is carried out with the aim of monitoring before delivery, especially aimed at the growth and development of the fetus in the womb. The risk of maternal death during pregnancy can be anticipated by performing ANC. K1 and K4 visits are still low, this is related to the attitude of pregnant women to the importance of ANC. The purpose of the study was to determine the relationship between the attitudes of pregnant women and adherence to ANC visits. This type of research is descriptive analytic with a cross sectional. The time of the research was carried out in January-March 2022. The place of research was carried out in Karya Indah Village. The sample in this study were 30 respondents with total sampling technique. The research instrument used a questionnaire. Data analysis was carried out univariate and bivariate. Univariate results showed that the majority of respondents' attitudes were positive with a percentage of 62.5%. Bivariate analysis using Chi-square found, there was a relationship between attitudes towards ANC visits with p value (0.000 <0.05). It is expected that pregnant women will adopt a positive attitude to comply with ANC visits in order to improve the health and welfare of the mother and fetus